Utilization of iron ions to improve the depressive efficiency of tartaric acid on the flotation separation of scheelite from calcite. (1st July 2021) - Dong, Liuyang; Jiao, Fen; Qin, Wenqing; Wei, Qian
Graphical abstract: Highlights: Scheelite and calcite had good floatability using sodium oleate as collector. The selectively depression behavior of TA/Fe 3+ was investigated. Fe 3+ and TA was co-adsorbed on the surface of calcite. Flotation separation of scheelite from calcite was achieved using TA/Fe 3+ . Abstract: Scheelite and calcite have similar surface physical and chemical properties and the same calcium ion active sites in the slurry. In order to achieve the flotation separation of the two minerals, high-efficiency flotation depressants are required. In this work, the mixed application of ferric ions (Fe 3+ ) and small molecular organic chelating reagent tartaric acid (TA) was used to explore its depressive effect on the flotation separation of scheelite from calcite. The flotation separation effect of scheelite from calcite under the condition of mixed depressant Fe 3+ /TA was studied through microflotation experiments and artificial mixed mineral experiments. The selective adsorption mechanism of the mixed depressant on the two minerals was revealed by zeta potential experiments, solution chemical analysis, thermodynamic analysis, adsorption experiments and X-ray photoelectron spectroscopy (XPS) analysis. The flotation experiments indicated that the mixed depressant can efficiently realize the flotation separation of scheelite from calcite. The mechanism experiments revealed that the mixed depressant had a stronger co-adsorption on the surface of calcite. The pre-adsorption of iron ions provided much adsorption sites for the adsorption of depressant TA, which increased the adsorption amount of TA and iron ions on the surface of calcite, and it hindered the further adsorption of the collector sodium oleate (NaOL). The mixed depressant TA/Fe 3+ adsorbed on the surface of calcite mainly existed preferentially in the form of the chelate FeL2 − .